Tissue-specific I-Smad mechanisms revealed by structure-function analysis in Drosophil - Sulkowski, Mikolaj; Simoncek, Ani; Sviridoff, Steven; Graichen, Noah; Hays, Joshua (Zenodo (CERN European Organization for Nuclear Research), 2026)
Data from publication in Life Science Alliance
Keywords: Alliance; Context (archaeology); Set (abstract data type); dept.bio